Circadian rhythms in pediatric craniopharyngioma - Kamara, Dana; Crowley, Stephanie J.; Crabtree, Valerie McLaughlin; Hancock, Donna; Li, Yimei; Darji, Himani; Semko, Joshua; Wise, Merrill S.; Merchant, Thomas E.; Mandrell, Belinda N. (Frontiers in Sleep, 2023)
Craniopharyngioma is a brain tumor arising in the region of the hypothalamic-pituitary axis. Children and adolescents with craniopharyngioma have high survival rates, but often experience significant morbidity, including high rates of sleep disorders. Vulnerabilities to circadian disruption are present in this population, but little is known about circadian health. We present exploratory circadian findings from a prospective trial at a single center. Data presented here are from the baseline timepoint. Fifty-three patients between the ages of 7 and 20 years provided salivary melatonin samples, following surgical resection and prior to completion of proton therapy, when indicated. We estimated dim light melatonin onset (DLMO) and collected additional sleep data from actigraphy, overnight polysomnography, and the multiple sleep latency test. Almost half of participants did not have a valid DLMO estimate during the sampling window, with most being above the threshold at the first sample timepoint. Those with greater disease severity variables (greater hypothalamic involvement and the presence of diabetes insipidus) were significantly more likely to have missed DLMO. For those with valid estimates, DLMO timing correlated with BMI and other sleep variables, including mean sleep latency values on the MSLT. These findings suggest that a subset of those with pediatric craniopharyngioma may experience a phase advance and that this may relate to poorer prognostic indicators. Furthermore, circadian timing correlates with other sleep and health factors. Further research with earlier sampling is needed to better understand circadian rhythms in pediatric craniopharyngioma and associations with other health and disease variables.